(untitled) - Hamilton, Alexander (New York, N.Y., 1999)
An authoritative analysis of the Constitution of the United States and an enduring classic of political philosophy.
Keywords: Constitutional history,Constitutional history,Constitutional law,Luật Hiến pháp,Lịch sử hiến pháp; United States,United States,United States,Hoa Kỳ,Hoa Kỳ